PENCEGAHAN HIV/AIDS MELALUI COLLABORATIVE GOVERNANCE ANTARA PEMERINTAH, LEMBAGA SWADAYA MASYARAKAT, DAN MASYARAKAT DI PROVINSI DKI JAKARTA - Agung Rheza Fauzi; Amy Yayuk Sri Rahayu (Yogyakarta State University, 2018)
The DKI Jakarta AIDS Commission (KPA) seeks to prevent HIV / AIDS cases through collaborative governance between the Government, Non-Governmental Organizations (NGOs), and the community. This collaborative governance is strengthened through Pergub Number 231 Year 2015 concerning the Organization and Work Procedure of the DKI Jakarta Provincial KPA and Regional Regulation Number 5 Year 2008 concerning HIV AIDS Management. This research was conducted to analyze the collaborative process of HIV AIDS prevention in DKI Jakarta Province. In addition, this study aims to provide recommendations for effective collaborative governance in the context of HIV AIDS prevention in DKI Jakarta Province. This study uses descriptive qualitative research methods that describe the collaborative process of HIV AIDS prevention in DKI Jakarta Province. This research uses collaborative governance theory that focuses on the collaboration process. Based on the research, it is known that collaborative governance has been established between the Government, NGOs and the Community. However, it has not been effective because of the lack of roles of working groups and NGOs that still depend on donor agencies.